An investigation into potential causes of the anomalistic feature observed by the Rosetta Alice spectrograph around 67P/Churyumov–Gerasimenko. (August 2016) - Noonan, John; Schindhelm, Eric; Parker, Joel Wm.; Steffl, Andrew; Davis, Michael; Stern, S. Alan; Levin, Zuni; Kempf, Sascha; Horanyi, Mihaly
Abstract: The Alice far-ultraviolet spectrograph in operation around the comet 67P/Churyumov–Gerasimenko on the Rosetta spacecraft experiences an anomalistic feature (AF) that is ubiquitous at comet separations less than 450 km. This feature is highly temporally variable and displays no relation to any studied parameters with the exception of comet separation. This paper tests several possible causes with simulations and finds that positive ions produce a partial explanation for the anomaly, but still finds no definitive source of the AF. Abstract : Highlights: Rosetta Alice experiences an anomalistic FUV feature near comet 67P/CG. The anomaly is temporally variable and affects a large fraction of observations below comet separations of 450 km. The energies of the particles causing the anomaly are greater than FUV photons. Simulations made in an attempt to understand the source of the anomaly have produced interesting but inconclusive results.